Fairy tales magic story cube using augmented reality - Ngu, Wen Woo (Universiti Malaysia Sarawak, (UNIMAS), 2009)
The advancement of computer in term of its technology has given rise to more sophisticated and smarter computers. These have given birth to Augmented Reality (AR) technology. AR enables users to view vil1ual 3D model in the real world environment real-time. This project describes an AR application in the field of storytelling using cube. Users can continuously unfold the cube to display the desired scene. 3D models are created and rendered in VR environment to provide users a unique way of presenting story with virtual models and animations.